A de novo reference assembly of the yellow mangrove Ceriops zippeliana genome. Issue 4 (2nd February 2022) - Pootakham, Wirulda; Sonthirod, Chutima; Naktang, Chaiwat; Kongkachana, Wasitthee; U-thoomporn, Sonicha; Phetchawang, Phakamas; Maknual, Chatree; Jiumjamrassil, Darunee; Pravinvongvuthi, Tamanai; Tangphatsornruang, Sithichoke
Abstract: Mangroves are of great ecological and economical importance, providing shelters for a wide range of species and nursery habitats for commercially important marine species. Ceriops zippeliana (yellow mangrove) belongs to Rhizophoraceae family and is commonly distributed in the tropical and subtropical coastal communities. In this study, we present a high-quality assembly of the C. zippeliana genome. We constructed an initial draft assembly of 240, 139, 412 bases with an N50 contig length of 564, 761 bases using the 10x Genomics linked-read technology. This assembly was further scaffolded with RagTag using a chromosome-scale assembly of a closely related Ceriops species as a reference. The final assembly contained 243, 228, 612 bases with an N50 scaffold length of 10, 559, 178 Mb. The size of the final assembly was close to those estimated using DNA flow cytometry (248 Mb) and the k- mer distribution analysis (246 Mb). We predicted a total of 23, 474 gene models and 21, 724 protein-coding genes in the C. zippeliana genome, of which 16, 002 were assigned gene ontology terms. We recovered 97.1% of the highly conserved orthologs based on the Benchmarking Universal Single-Copy Orthologs analysis. The phylogenetic analysis based on single-copy orthologous genes illustrated that C. zippeliana and Ceriops tagal diverged approximately 10.2 million years ago (MYA), and their last common ancestor and Kandelia obovata diverged approximately 29.9 MYA. The high-quality assembly of C. zippeliana presented in this work provides a useful genomic resource for studying mangroves' unique adaptations to stressful intertidal habitats and for developing sustainable mangrove forest restoration and conservation programs.